Interpreting Myanmar A Decade of Analysis - Selth, Andrew (ANU Press, 2020)
Since the abortive 1988 pro-democracy uprising, Myanmar (formerly Burma) has attracted increased attention from a wide range of observers. Yet, despite all the statements, publications and documentary films made about the country over the past 32 years, it is still little known and poorly understood. It remains the subject of many myths, mysteries and misconceptions. Between 2008 and 2019, Andrew Selth clarified and explained contemporary developments in Myanmar on the Lowy Institute's internationally acclaimed blog, The Interpreter. This collection of his 97 articles provides a fascinating and informative record of that critical period, and helps to explain many issues that remain relevant today.